2017
DOI: 10.22256/pubvet.v11n9.848-853
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos anatómicos y morfométricos del cráneo de Diopsittaca nobilis Linnaeus, 1758

Abstract: RESUMO.As aves da ordem Psittaciformes estão entre as mais criadas como pet, o que consequentemente aumenta a procura por atendimento médico veterinário especializado em aves e, para tal, o estudo e conhecimento da anatomia destes animais se torna essencial. De outra forma, a morfologia craniana é fundamental na identificação de espécie de animais com características morfológicas externas semelhantes. Buscou-se obter dados referentes ao crânio de Diopsittaca nobilis, para contribuir com o conhecimento anatômic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…The data from this study on male chicken are a bit different in comparison with those of Amazona aestiva species, which represents 22.6% of the skull maximum caudal width, and of Diopsittaca nobilis species with 20.2% (Souza et al, 2017).…”
Section: Discussioncontrasting
confidence: 58%
“…The data from this study on male chicken are a bit different in comparison with those of Amazona aestiva species, which represents 22.6% of the skull maximum caudal width, and of Diopsittaca nobilis species with 20.2% (Souza et al, 2017).…”
Section: Discussioncontrasting
confidence: 58%
“…The distance between the orbits represented 71.2% of the maximum skull width and 77.3% of the maximum skull caudal width. Souza et al (2017a) studied Diopsittaca nobilis (Psittaciformes) and reported that these same proportions were, respectively, 71.1% and 74.4%, and did not present significantly different values. A large skull is associated to a larger area of muscle insertion in Falconidaes, that positively influences their way of feeding, and is a mechanical advantage (SUSTAITA, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…The zona flexoria craniofacialis in a study by Souza et al (2017a) for Diopsittaca nobilis represented 62.2% of the maximum skull width and 65.1% maximum caudal width. In Forpus xanthopterygius (SOUZA et al, 2017b) the craniofacial flex zone represented 54.6% of the maximum skull width and 55.0% of the maximum caudal width.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations